Anatomical Origins of Radial Artery Perforators Evaluated Using Color Doppler Ultrasonography - Onode, Ema; Takamatsu, Kiyohito; Shintani, Kosuke; Yokoi, Takuya; Uemura, Takuya; Okada, Mitsuhiro; Kazuki, Kenichi; Nakamura, Hiroaki (Journal of Reconstructive Microsurgery, 2016)
Background The radial artery perforator (RAP) flap has been widely used for covering hand and forearm defects, and real-time accurate perforator mapping is important in planning and elevating the perforator flap. The origins of perforators, especially the superficial and ulnar perforators, arising from the radial artery are very important in the elevation of the RAP flap. Recently, color Doppler ultrasonography (US) using a higher frequency transducer has been developed for high-quality detection of lower flow in smaller vessels. This study aimed to identify the anatomical locations and origins of perforators arising from the radial artery using color Doppler US in healthy volunteers.Methods Twenty forearms of 10 volunteers were examined.Results In total, 120 perforators arising from the radial artery were identified 15 cm proximal to the distal wrist crease, with an average of six perforators per forearm. More than half the perforators (n = 72, 60%) were located within 50 mm proximal to the distal wrist crease. Regarding the perforator origins in the axial view, 40 perforators (33%) were located in the radial aspect of the radial artery, 47 (39%) in the ulnar aspect, 15 (13%) in the superficial aspect, and 18 (15%) in the deep aspect. In total, 62 (52%) perforators were located in the superficial and ulnar areas, which are important in nourishing and elevating the RAP flap.Conclusion We are the first to evaluate RAP using color Doppler US. This noninvasive, convenient, and real-time technique could be useful for preoperative planning and reliably elevating the RAP flaps.
Keywords: ultrasonography; perforator; radial artery